ANALISIS RELASI/HUBUNGAN ORGANISASI NON PEMERINTAHAN DALAM ADVOKASI KEBIJAKAN LINGKUNGAN HIDUP KOTA PEKALONGAN (Studi Komunitas Peduli Kali Loji (KPKL) dalam Penanganan Limbah Batik dan Sampah Pada Sungai Kota Pekalongan) - Suci Rejeki; R Slamet Santoso; Retna Hanani (Journal of Public Policy and Management Review, 2021)
Pekalongan is an area that has many rivers in the middle of the city. As a city, Pekalongan City still faces problems in the form of waste and garbage pollution. Where Pekalongan is a city of batik and the batik industry is the main supporter of the community's economy. It is known that the government's efforts to overcome these problems have not been able to overcome the problem optimally. For this reason, the existence of the Komunitas Peduli Kali Loji (KPKL) as one of the Non-Governmental Organizations is important. The Komunitas Peduli Kali Loji (KPKL) has an involvement to assist the government in overcoming environmental problems in Pekalongan City, as a result of the very critical condition of the river. Based on this involvement, the researchers wanted to see how the relationship between KPKL and the Government (City, Regency, Province and Central). So this research was conducted to describe and analyze the relationship between KPKL and the Government in the context of handling the problem of batik waste and garbage in the Pekalongan City River. The approach used is descriptive qualitative with data collection techniques in the form of interviews, field observations, documentation and literature study. The results of the study indicate that the relations/relationships between KPKL and the Government include: First, relations/relationships that involve KPKL in Government activities; Second: the relationship/relationship between KPKL and the Government is cooperative in that this relationship is mutually beneficial, a partnership relationship where this relationship is very participatory in the context of development to conflictive relationships, taking distance so as to limit the space for movement; Third: the relationship/relationship of KPKL as a parallel partner of the Government.